TOKOH ADELINE YEH MAH DALAM NOVEL FALLING LEAVES: PENDEKATAN PSIKOLOGI SASTRA - Wahyuni Wumu (TELAGA BAHASA, 2017)
This paper aimed to examine the personality of Adeline's character, hispsychological conflict and her attitude in dealing with various conflicts inher life in the memoir of Falling Leaves based on Sigmund Freud'spsychoanalytic personality theory. This paper used the approach of literarypsychology. From the analysis, it was found that Adeline's figure wasalways trying to please her parents, a smart, principled, prestigious andresilient person even she must through hard time, such as the necessity ofsimple life even though she was rich, and concerned with bad experiences inher life because of the presence of her step mother and stepsisters,evethough she came from a wealthy family.